Nefazodone Atypical Antidepressant Associated Hepatotoxicity- Drug Induced Liver Injury (DILI) A Possible Genotoxic Effect(s) - Mustafa Tariq Sakin (Journal of Global Pharma Technology, 2016)
The atypical antidepressant Nefazodone used in different concentrations (2.5, 5, 10 µg/ml ) to study its genotoxic effects on HepG2 cell line by using single cell gel electrophoresis assay (Comet) and spectral karyotyping test (SKY).The results showed that Nefazodone causes a significant increment in the three important parameters (tail length, percent of DNA in tail and tail moment) of comet assay for the three used concentrations in a dose-dependent manner when compared with negative control (p˂0.01). SKY analysis was performed at the concentration of (10 µg/ml). Both the treated and negative control cells showed abnormal chromosomal number (44-54 XY) per cell, common chromosomal rearrangements and other abnormalities in the majority of cells analyzed. As a result Nefazodone has no chromosomal aberration at 10µg/ml and the comet assay results conceder as false positive.Keywords: Nefazodone, Genotoxicity, HepG2 cell line.